2023
DOI: 10.1017/cft.2023.1
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of change in Arctic fjord socio-ecological systems: Examples from the European Arctic

Abstract: Fjord systems are transition zones between land and sea, resulting in complex and dynamic environments. They are of particular interest in the Arctic as they harbour ecosystems inhabited by a rich range of species and provide many societal benefits. The key drivers of change in European Arctic (i.e. Greenland, Svalbard, and Northern Norway) fjord socioecological systems are reviewed here, structured into five categories: cryosphere (sea-ice, glacier mass balance, glacial and riverine discharge), physics (seawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 171 publications
0
7
1
Order By: Relevance
“…This is found in Fig. 2 of Schlegel et al (2023), which shows the key relationships between drivers and the direction of their interactions, as determined from the literature. Because the aim of this dataset is to allow for investigations of the interactions between drivers within a given Arctic fjord socioecological system, we did not compare data across sites.…”
Section: Relationships Between Driversmentioning
confidence: 95%
See 3 more Smart Citations
“…This is found in Fig. 2 of Schlegel et al (2023), which shows the key relationships between drivers and the direction of their interactions, as determined from the literature. Because the aim of this dataset is to allow for investigations of the interactions between drivers within a given Arctic fjord socioecological system, we did not compare data across sites.…”
Section: Relationships Between Driversmentioning
confidence: 95%
“…sea water or degrees Celsius) from the list of variables. While all of the data originally identified were aggregated, a literature review performed for this same project revealed that the important interactions within socio-ecological systems would be better expressed as broad drivers rather than individual variables (Schlegel et al, 2023). In reaction to this, further pruning of the dataset outlined here revealed that many of the variables from the initial list had little to no available data.…”
Section: Categories → Drivers → Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Microorganisms, the key players in marine primary productivity and recycling organic matter, form the base of the marine food web and drive major biogeochemical cycles such as carbon and nitrogen 7 . They form unique, regional communities in sub-Antarctic fjords 8 , whose occurrence and/or maintenance is of high interest in understanding the coupling between biodiversity and physical dynamics of Arctic ecosystems 9 . Analysis of microbes and their role in Arctic and sub-Arctic ecosystems requires trait-based approaches, especially considering the large size range (micro-, nano-, and picoplankton) and differential ecological roles of microbes 10 .…”
Section: Introductionmentioning
confidence: 99%